Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.psc.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology of Sleep and Wakefulness

Abstract: SYNOPSIS Since the discovery of Rapid Eye Movement (REM) sleep in the late 1950s, identification of the neural circuitry underlying wakefulness, sleep onset and the alternation between REM and non-REM (NREM) sleep has been an active area of investigation. Synchronization and desynchronization of cortical activity as detected in the electroencephalogram (EEG) is due to a corticothalamocortical loop, intrinsic cortical oscillators, monoaminergic and cholinergic afferent input to the thalamus, and the basal foreb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(105 citation statements)
references
References 325 publications
1
92
0
7
Order By: Relevance
“…The serotonin neurotransmitter system is particularly relevant to depression [48] in addition to having a role in sleep-wake regulation [49], making it a logical candidate gene target. Multiple studies have examined the classic 5-HTTLPR polymorphism (short or long allele) (e.g., [50,51]), as well as polymorphisms in monoamine oxidase A (MAO-A) (e.g., [52]), which is an enzyme that breaks down serotonin, thus contributing to its availability in the brain [48].…”
Section: Measured Gene Studies Of Insomniamentioning
confidence: 99%
“…The serotonin neurotransmitter system is particularly relevant to depression [48] in addition to having a role in sleep-wake regulation [49], making it a logical candidate gene target. Multiple studies have examined the classic 5-HTTLPR polymorphism (short or long allele) (e.g., [50,51]), as well as polymorphisms in monoamine oxidase A (MAO-A) (e.g., [52]), which is an enzyme that breaks down serotonin, thus contributing to its availability in the brain [48].…”
Section: Measured Gene Studies Of Insomniamentioning
confidence: 99%
“…In the last decades, accumulating reports have suggested that the sleep-wake cycle is under control of a complex neurobiological network which includes neuroanatomical, neurochemical and molecular components (Murillo-Rodrı´guez et al, 2012;Zeitzer, 2013;Saper, 2013;Fernandes et al, 2015;Schwartz and Kilduff, 2015). In parallel, further complicatedness in the understanding of sleep mechanism has been pointed-out due to that circadian and homeostatic factors influence sleep processes (Curie et al, 2013Houben et al, 2014;Borbely et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, waking is modulated by the activity of diverse neurotransmitter systems such as noradrenaline, dopamine, serotonin, acetylcholine, histamine and hypocretin [3,[15][16][17][18][19][20][21][22][23][24] (Fig. 2).…”
Section: Hypocretin As Regulator Of Waking Statementioning
confidence: 99%